Energy efficient green building design utlilising renewable energy and low-carbon development technologies - Sagar; Arya Yogendra; Singhal Poonam (Science and Technology for Energy Transition)
The core issue these days is to reduce carbon dioxide (CO2) emission and prevent the hole in the ozone layer. Numerous emerging environmental crises successfully tackled by coordinated global efforts in the past few years. Despite this, the present climate emergency is a much more serious threat than anything we have ever encountered and requires much more action consequently. Today, more attention is paid on green buildings in the society, which will make use of the sustainable and energy-efficient buildings a necessity for future generations. Hence, this paper proposes a novel design model of an energy-efficient residential green building with low carbon emission to maintain the health and enhances the productivity and living standards of inhabitants. Green building technology is utilised to enhance energy efficiency and lower carbon emission. This design considers green, recyclable, and eco-friendly building materials, which are beneficial for human health and comply with relevant Indian standards and building codes. This building design proposes Renewable Energy Sources (RES) integrated with the power grid, although RES powers most of the load of the proposed green building. The suggested green building design shows effective results, i.e., building energy consumption has reduced by 50.54%, total energy consumption cost has reduced by 57.41%, and CO2 emission per month has reduced by 50.54%. In addition, stormwater-harvesting system is proposed to collect 54,322.23 L of rainwater annually, which helps in water conservation and contributes to improve the groundwater level. The proposed solid waste management plan has contributed to the achievement of regional and national Sustainable Development Goals (SDGs). Finally, there are some suggestions to promote the use of green buildings for sustainable development.